2015
DOI: 10.3892/ijmm.2015.2289
|View full text |Cite
|
Sign up to set email alerts
|

Amantadine inhibits cellular proliferation and induces the apoptosis of hepatocellular cancer cells in vitro

Abstract: Hepatocellular carcinoma (HCC) is one of the most aggressive malignancies worldwide, and its incidence associated with viral infection has increased in recent years. Amantadine is a tricyclic symmetric amine that can effectively protect against the hepatitis C virus. However, its antitumor properties remain unclear. In the present study, the effects of amantadine on tumor cell viability, cell cycle regulation and apoptosis were investigated. The growth of HepG2 and SMMC‑7721 cells (HCC cell lines) was detected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Amantadine, which acts on the viral M2 protein, thus hindering virus uncoating once it is taken inside the cell by endocytosis, was previously reported to suppress proliferation and to induce apoptosis in hepatocellular carcinoma cells [ 121 ]. Pleconaril integrates into the capsid of picornaviruses, preventing the virus from attaching to cellular receptors and preventing RNA release into the cell [ 122 ].…”
Section: Selected Repurposing Candidates For the Treatment And/or Prementioning
confidence: 99%
“…Amantadine, which acts on the viral M2 protein, thus hindering virus uncoating once it is taken inside the cell by endocytosis, was previously reported to suppress proliferation and to induce apoptosis in hepatocellular carcinoma cells [ 121 ]. Pleconaril integrates into the capsid of picornaviruses, preventing the virus from attaching to cellular receptors and preventing RNA release into the cell [ 122 ].…”
Section: Selected Repurposing Candidates For the Treatment And/or Prementioning
confidence: 99%
“…In the present study, the bifunctional species L 2 H has been conjugated to the known drug amantadine to obtain the new ligand L 2Ad , which has been used as a chelator for the synthesis of the new Cu complexes 1 – 5 (Figure ) to be evaluated as potential agents for the treatment of glioblastoma. Amantadine was selected as a bioactive molecule since it has recently been demonstrated to show from moderate to good antiproliferative effects in different human tumor cell lines, including hepatocarcinoma, melanoma, and glioblastoma cells. Moreover, Pt-based complexes functionalized with amantadine have already been reported to display promising cytotoxic activity against various human tumor cell lines . Finally, amantadine consists of a primary amine group suitable to be conjugated to the carboxylic group of the bifunctionalizable species L 2 H and the bioversatile adamantyl scaffold, which characterizes several derivatives identified as anticancer agents. , …”
Section: Introductionmentioning
confidence: 99%
“…Amantadine increased the expression of aromatic amino acid decarboxylase (AADC) [ 12 ]. In vitro experiments revealed that amantadine inhibits proliferation of HepG2 and SMMC-7721 cells by arresting the cell cycle at the G0/G1 phase [ 13 ]. Amantadine also reduces Bcl-2 and increases Bax proteins and mRNA levels in HepG2 and SMMC-7721 cell lines, which leads to the intensification of apoptosis in liver cancer cells [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…In vitro experiments revealed that amantadine inhibits proliferation of HepG2 and SMMC-7721 cells by arresting the cell cycle at the G0/G1 phase [ 13 ]. Amantadine also reduces Bcl-2 and increases Bax proteins and mRNA levels in HepG2 and SMMC-7721 cell lines, which leads to the intensification of apoptosis in liver cancer cells [ 13 ]. Amantadine seems to be a drug with potential anti-cancer activity due to the fact that the drug could inhibit cell growth by modulating cyclin D1, cyclin E, CDK2 and inducing apoptosis via regulation of Bax and Bcl-2 proteins [ 13 ].…”
Section: Introductionmentioning
confidence: 99%